2015
DOI: 10.1111/ina.12270
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to measure the gas‐phase SVOC concentration adjacent to a material surface

Abstract: Assessing human exposure to semivolatile organic compounds (SVOCs) emitted from materials and products is difficult because methods are not available to easily measure the key emission parameters. A simple method based on a passive sampling technique was thus developed to measure the gas-phase SVOC concentration (y ) immediately adjacent to the material surface in a consumer product. The method employs standard stainless steel thermal desorption tubes, with values of y and an additional unknown parameter, K, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 32 publications
1
55
1
Order By: Relevance
“…Further improvement to the structure of the chamber could be made to measure y 0 without requiring flat source materials, as has been addressed by Wu et al 25 Second, the measured y 0 strongly depends on D a . First, it is only applicable for flat and relatively soft source materials.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Further improvement to the structure of the chamber could be made to measure y 0 without requiring flat source materials, as has been addressed by Wu et al 25 Second, the measured y 0 strongly depends on D a . First, it is only applicable for flat and relatively soft source materials.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…First, it is only applicable for flat and relatively soft source materials. Further improvement to the structure of the chamber could be made to measure y 0 without requiring flat source materials, as has been addressed by Wu et al 25 Second, the measured y 0 strongly depends on D a . Even though the measured and estimated results for D a have demonstrated that equation (6) can provide accurate results, a more comprehensive study of the error of y 0 introduced by the error of D a is required.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
See 3 more Smart Citations